Antioxidant Candidates in Deep Eutectic Solvent Extract of Choline Chloride-Oxalic Acid from Sago Bark (Metroxylon sagu L. Rottb) - Hamdani, Ulfah Zakiyah; Yanti, Rosmalah (Indonesian Journal of Chemical Science, 2025)
Waste deposits from sago (Metroxylon sagu L. Rottb.) starch extraction from sago trunks in Palopo City, Luwu Regency, North Luwu Regency and East Luwu Regency which are part of the Tana Luwu region are quite abundant. Many studies on the utilization of liquid waste from this process have been published. In contrast, the utilization of solid waste has not been widely carried out. In addition, studies on the identification of compounds from the extraction of sago bark waste using environmentally friendly solvents such as deep eutectic solvent (DES) are still minimal. The DES used was DES Choline Chloride-Oxalic Acid with a mole ratio of 1:2. The success of DES synthesis was confirmed by FT-IR. Extraction was carried out using the sonication method for 30 minutes at 50 W, room temperature, with a ratio of 80 mesh sago bark to DES of 1:10 (g/ml). The extract was filtered with filter paper with a pore diameter of 2.5 µm. Screening of compounds in the filtrate through GC-MS analyses. DES was successfully synthesized while still showing the main functional groups. GC-MS analysis of the filtrate showed that there were 8.36% squalene-like compound; 5.37% n-hexadecanoic acid-like compound and other compounds (with solvent exception) contained ≤1%.